Determinants of Firm Value: A Study on Islamic Banking in Indonesia - Mochammad Ridwan; Erik Syawal Alghifari; Winwin Yadiati; Karisma Azahra Hidayah (Faculty of Economics, Universitas Sriwijaya, 2023)
This study attempts to measure the effect of Islamic corporate governance and Islamic social responsibility on firm value and to analyse the moderation role of profitability. Data from 12 Islamic commercial banks registered in Indonesia was taken from 2017 to 2021 and analysed using a panel data regression approach with the generalized least squares approach and model robustness testing using the robust least squares analysis method. Strong Islamic corporate governance highlights the benefits of ethical governance and increases the value of sharia-compliant banks. The long-term character of corporate social responsibility is demonstrated by the fact that some Islamic social responsibility activities do not necessarily have a positive influence on the firm value banking sector in Indonesia. High profitability strengthens Islamic corporate governance and has a beneficial impact on firm value, emphasising the interdependence between governance and financial performance. High profitability may reduce the beneficial impact of Islamic social responsibility on firm value, perhaps due to the perception of corporate social responsibility initiatives as being motivated by profit.